A STUDY ON INCREMENTAL MINING OF FREQUENT PATTERNS - M, Dutta Borah1; R, Jindal2 (جامعة الوادي university of eloued, 2018)
Data generated from both the offline and online sources are incremental in nature. Changes in the underlying database occur due to the incremental data. Mining frequent patterns are costly in changing databases, since it requires scanning the database from the start. Thus, mining of growing databases has been a great concern. To mine the growing databases, a new Data Mining technique called Incremental Mining has emerged. The Incremental Mining uses previous mining result to get the desired knowledge by reducing mining costs in terms of timeand space. This state of the art paper focuses on Incremental Mining approaches and identifies suitable approaches which are the need of real world problem
artical
Keywords: Data Mining, Frequent Pattern, Incremental Mining, Frequent Pattern Minung, High Utility Mining, Constraint Mining